Thermal Injuries in Children: A Literature-Based Overview - Natalia Wierzejska; Aneta Michalczewska; Agnieszka Fugas; Magdalena Pach; Agnieszka Nowak; Zuzanna Chmielowiec; Alicja Partyka; Mariola Dziedzic; Karolina Smykiewicz; Justyna Dobrzańska (Kazimierz Wielki University, 2024)
Burns are a significant cause of morbidity and mortality in children. While the majority of pediatric burns are not life-threatening, they can have a significant impact on a child's physical and psychological health. They pose a major social and financial burden, particularly in developing countries. The management of pediatric patients with thermal injuries requires a complex and multifaceted approach. Pediatric burns constitute approximately 40-50% of all reported cases of severe burns. The most common etiologies of pediatric burns include scalds, contact burns, flames, and chemicals. From 80% to 90% of burns occurred at home and were accidental. Despite advancements in treatment, severe burns can lead to life-threatening complications, such as sepsis, multisystem organ failure, and hypermetabolic response or even death. This article aims to provide a literature-based overview of pediatric burn trauma, outlining its unique characteristics, etiology, epidemiology, classification, and initial management.